A Brief Overview of Oxidative Stress in Adipose Tissue with a Therapeutic Approach to Taking Antioxidant Supplements - Shima Taherkhani; Katsuhiko Suzuki; Ruheea Taskin Ruhee (Antioxidants, 2021)
One of the leading causes of obesity associated with oxidative stress (OS) is excessive consumption of nutrients, especially fast-foods, and a sedentary lifestyle, characterized by the ample accumulation of lipid in adipose tissue (AT). When the body needs energy, the lipid is broken down into glycerol (G) and free fatty acids (FFA) during the lipolysis process and transferred to various tissues in the body. Materials secreted from AT, especially adipocytokines (interleukin (IL)-1β, IL-6, and tumor necrosis factor-α (TNF-α)) and reactive oxygen species (ROS), are impressive in causing inflammation and OS of AT. There are several ways to improve obesity, but researchers have highly regarded the use of antioxidant supplements due to their neutralizing properties in removing ROS. In this review, we have examined the AT response to OS to antioxidant supplements focusing on animal studies. The results are inconsistent due to differences in the study duration and diversity in animals (strain, age, and sex). Therefore, there is a need for different studies, especially in humans.